THE LEGAL IMPACT OF PALM OIL PLANTATIONS ON MARGINALISED COMMUNITIES: EFFECTS ON LAND ACCESS, INVOLVEMENT IN THE ECONOMIC VALUE CHAIN, AND STRATEGIES FOR IMPROVING SOCIO-ECONOMIC WELFARE - Gunawan Widjaja (Adisam Publisher, 2025)
This study analyses the legal impact of oil palm plantations on marginalised communities in Indonesia, focusing on the effects on land access, involvement in the economic value chain, and strategies for improving socio-economic welfare. Using a qualitative legal-empirical approach, the study found that regulations such as Law No. 39/2014 on Plantations and Law No. 5/1960 on Basic Agrarian Principles failed to protect the customary rights of indigenous peoples due to the prioritisation of HGU (right to cultivate) that ignored FPIC (free, prior and informed consent), causing massive agrarian conflicts and economic marginalisation where communities only capture 10-20% of the value of the supply chain as primary labourers. The proposed reform strategies include strengthening 50:50 plasma partnerships, agroforestry diversification, women's empowerment through CSR, and market digitalisation to increase income by up to 40%, in line with Constitutional Court Decision No. 35/PUU-X/2012 and the ISPO 2030 target.